(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
The cartographic contributions of the peoples subjected to colonization and marginalized by the visual regimes of the West begin to come to light. These practices of counter-cartographic representation located on the limits of traditional cartography, have been and are still used today as a tool of resistance with a view to recovering a political presence made invisible in the colonial and neo-colonial narratives. In this article, we will focus on the variables of three cases of decolonial graphic productions of indigenous and Afro-descendant women in order to understand these alternative practices as critical propositions about the reality of themselves in their environment. For these reasons, they can contribute to revisiting History, by incorporating their bodies as historical and active subjects in the transformation of past and present reality.